PENGARUH PEMBELAJARAN STRATEGI METAKOGNITIF BERBANTUAN AI TERHADAP KEMAMPUAN PEMECAHAN MASALAH FISIKA SISWA PADA MATERI USAHA DAN ENERGI - Aiman Alhabasiah, Umu; Khoiri, Ahmad; Imam Agus Faisal, Vava (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Senior high school students’ physics problem-solving ability on the topic of work and energy remains relatively low, as students tend to memorize formulas without understanding the underlying physical meaning of the problems they face. This study aimed to examine the effect of AI-assisted metacognitive strategy instruction on the physics problem-solving ability of eleventh-grade students on the topic of work and energy at SMA Takhassus Al-Qur’an Wonosobo. A quantitative quasi-experimental method with a nonequivalent control group design was employed, involving 46 eleventh-grade students divided into an experimental class (23 students) and a control class (23 students). Problem-solving ability was measured using an essay test based on four indicators of Polya’s problem-solving steps. Data were analyzed using normalized gain (N-Gain) scores and an independent sample t-test at a 5% significance level. The results showed that the experimental class obtained an N-Gain of 0.75 (high category), higher than the control class at 0.33 (moderate category), and hypothesis testing revealed a significant difference between the two classes (p < 0.05). It can therefore be concluded that AI-assisted metacognitive strategy instruction significantly improves students’ physics problem-solving ability on the topic of work and energy.